Disputes over small territories : a study of the spatial, political and philatelic aspects of such disputes : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Arts in Geography at Massey University, Palmerston North, New Zealand - Dawson, Kenneth (Massey University, 2016)
“Most governments are now alive to the advertising and propaganda value of postage stamps” Sir Dudley Stamp (1966) Professor of Geography. Seventy years after the formation of the United Nations, the world continues to be plagued by civil disorder, territorial claims and border disputes. Currently, there are some 150 claims and disputes still outstanding. Previous published work has revealed that postage stamps have played a key ole in the propaganda associated with territorial disputes in Latin American countries. This dissertation aims to ascertain whether this finding holds true for disputes outside of Latin America and to what extent postage stamp propaganda can influence these various disputes. This study then describes and examines the background of 20 selected territorial claims and two special situations in small territories in Europe, European Colonies and Asia. The disputes form a cross section of those which have occurred over the last 125 years. A brief historical and geographical review is included along with the known causation and the actual or possible solution to each dispute. Written and visual evidence is collected and presented to illustrate the role played by postage stamps in the propaganda associated with these selected small territorial disagreements. When appropriate, the relevant postal history is described and postage stamp examples illustrated. The results indicate that, in the disputes studied, violence and loss of life was endemic at some stage in the dispute. Potential or real economic gain was not the obvious prime trigger factor which initiated the dispute. Further analysis of the findings indicates that postage stamps do play an important role in the propaganda associated with territorial claims in Europe, European Colonies and in Asia. Specific examples are identified in which the role of the stamp proved to be a key item in exacerbating the discord further. No clear evidence could be demonstrated to indicate that the effects differed significantly in geographic or political terms between Europe and her Colonies. There is some evidence that stamp usage for political purposes may be more frequently used in recent years than in the past. In Asia, Japan has not utilised stamps for propaganda purposes in her territorial disputes. Postage stamps are a powerful source of political propaganda and can play an important role in territorial claims.
Keywords: Postage stamps; Political aspects; Boundary disputes